New Strait Times, 09 June 2010 - Halim Said (The New Straits Times Press (M) Bhd, 2010)
Thousands of Buddhist devotees thronged the Subang Jaya Buddhist Association (SJBA) temple last Friday to mark the birth, enlightenment, and parinibbana of Gautama Buddha.